2012
DOI: 10.1002/adhm.201200075
|View full text |Cite
|
Sign up to set email alerts
|

Wound‐Healing with Mechanically Robust and Biodegradable Hydrogel Fibers Loaded with Silver Nanoparticles

Abstract: The objective of this study is to provide a novel synthetic approach for the manufacture of wound-healing materials using covalently cross-linked alginate fi bers loaded with silver nanoparticles. Alginate fi bers are prepared by wet-spinning in a CaCl 2 precipitation bath. Using this same approach, calcium cross-links in alginate fi bers are replaced by chemical cross-links that involve hydroxyl groups for subsequent cross-linking by glutaraldehyde. The cross-linked fi bers become highly swollen in aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 60 publications
(60 reference statements)
1
56
0
Order By: Relevance
“…Other authors showed that not only uncoated AgNPs sized 5-15 nm but also those with a diameter of ~20 nm accelerated re-epithelialization, enhanced migration of fibroblasts and reduced neutrophil and macrophage infiltration at the wound site in rodent models. 36,38,39 Histological evaluations revealed that TA-modified AgNPs sized 13 nm, and to a lesser degree, 10-65 nm unmodified AgNPs, maintained neutrophil infiltration at the wound site up to 14 days. In contrast, TA-modified 33 nm AgNPs significantly accelerated neutrophil disappearance during the remodeling phase.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed that not only uncoated AgNPs sized 5-15 nm but also those with a diameter of ~20 nm accelerated re-epithelialization, enhanced migration of fibroblasts and reduced neutrophil and macrophage infiltration at the wound site in rodent models. 36,38,39 Histological evaluations revealed that TA-modified AgNPs sized 13 nm, and to a lesser degree, 10-65 nm unmodified AgNPs, maintained neutrophil infiltration at the wound site up to 14 days. In contrast, TA-modified 33 nm AgNPs significantly accelerated neutrophil disappearance during the remodeling phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro and in vivo work has pointed toward the unprecedented ability of AgNP to reduce inflammatory macrophage and neutrophil infiltration, to inhibit the production of inflammatory cytokines, and to regulate the expression of metalloproteinases (Wright et al, 2002;Bhol and Schechter, 2007;Tian et al, 2007;Wong et al, 2009;Liu et al, 2010;Zhang et al, 2014). Thus, it stands that the incorporation of AgNP in biomaterial dressings is expected not only to add an antimicrobial element to the scaffold but also to further improve wound healing (Lu et al, 2012a;Neibert et al, 2012;Fan et al, 2014;Herron et al, 2014). For example, a chitosan-AgNP dressing by Lu et al significantly increased the healing rate of dermal wounds 10% of the body surface area in a rat model as compared to silver sulfadiazine or chitosan film alone while the percentage of silver dissemination away from the area of injury was lower for AgNP (Lu et al, 2012a).…”
Section: Nanomaterials As Therapeutic Agents For Skin Regenerationmentioning
confidence: 99%
“…, leading to an ordered conformational structure called ''egg-box'' array. The property of Alg hydrogels being sensitive to pH and calcium ions showed potential applications in the field of intelligent DDSs [20][21][22][23][24][25][26][27][28]. However, few studies about the controlling release of nano-silver regulated by the intelligent response of Alg have been reported in the field of antimicrobial wound dressing.…”
Section: Introductionmentioning
confidence: 99%